Multi-level issues in social systems - Yammarino, Francis J., 1954-; Dansereau, Fred, 1946- (Research in multi level issues ;, 2006)
This volume brings together a set of studies analyzing different aspects of food and agriculture in the Middle East and North Africa (MENA). This sector is of crucial importance to the MENA economies, especially in terms of employment. Agriculture is particularly important for the poor, both on the consumption side - a large part of their budget is allocated to food - and as a source of incomes as most of the poor live in rural areas where agriculture dominates. Agriculture production in MENA is severely constrained by water scarcity and low, irregular rainfall. Sustainability is a major concern in many parts of the region as the quality of land and water resources is deterioration and scarcity becomes more severe due to growing competition from other parts of the economy. The fact that the region relies on imports for a large share of its food consumption is a major concern for policymakers who view this as a threat to national food security and a source of political vulnerability. The studies included in this volume range from regional overview to micro studies. The chapters with a country focus cover issues that are recurrent in many MENA countries, giving them a broader relevance. The analyses cover policy issues in a wide range of areas - water, drought management, agriculture technology, producer and consumer subsidies, domestic food distribution, and foreign trade - and discusses how coordinated policies in these and other areas can contribute to more rapid, sustainable growth and poverty reduction.